All-optical carbon dioxide remote sensing using rare earth doped chalcogenide fibers. (November 2019) - Starecki, Florent; Braud, Alain; Doualan, Jean-Louis; Ari, Julien; Boussard-Plédel, Catherine; Michel, Karine; Nazabal, Virginie; Camy, Patrice
Highlights: CO2 sensors. Infrared spectroscopy. Rare-earth luminescence. Frequency conversion. Chalcogenide fibers. Abstract: As many fundamental spectroscopic signatures associated to gases of interest are in the 2.5 – 15 µm spectral range (4000–350 cm −1 ), gases can be detected using efficient infrared (IR) emissions from rare earth (RE) ions embedded into chalcogenide glasses, which are well-known for having low phonon energies. An all-optical IR fiber sensor for in-situ carbon dioxide monitoring was developed. The 4.3 µm mid-IR source probing the gas absorption in this sensor is a Dy 3+ doped GaGeSbS fluorescent chalcogenide fiber. Following the 4.3 µm partial absorption by CO2, a wavelength conversion from 4.3 µm to 808 nm is implemented using excited state absorption (ESA) mechanisms in Er 3+ doped GaGeSbS bulk glasses or fibers. This wavelength conversion allows the use of silica fibers to transport the 808 nm converted signal. This all-optical sensor with a sensitivity of few hundreds of ppm can be typically deployed over the kilometer range, making this tool suitable for field operations. The photon conversion principle used in this gas sensor could be implemented as a general mean to detect infrared radiations using visible or near-IR detectors instead of mid-infrared detectors.